Efeito protetor e cicatrizante gástrico do extrato de sementes de Lonchocarpus sericeus em roedores - Freire, Gabrielle de Paula (2023)
Gastric ulcers are a disease prevalent worldwide, and the drugs used to treat them, although effective, have side effects. An alternative therapy for this disease would be the use of preparations obtained from natural products. Lonchocarpus sericeus is a species popularly used as an anti-inflammatory and analgesic agent, as well as for the treatment of gastrointestinal disorders. In the present work, the protective and gastric healing effects of hexane extract of L. sericeus seeds (LsHE) were investigated. The chemical composition was determined and the main constituents were evaluated in silico. The gastroprotective potential was analyzed in ethanol- and indomethacin- induced gastric lesions in mice. In these models, mucus content and markers of oxidative stress and inflammation were studied. In addition, the effect of LsHE on possible signaling pathways and on gastric secretion was investigated. Its healing potential was analyzed in acetic acid-induced gastric lesions in rats. In addition, repeated-dose toxicity and markers of oxidative stress and inflammation were investigated. Eight components were identified in LsHE, the most important of which were oleic acid, palmitic acid, and behenic acid. In silico analysis predicted properties favorable for gastrointestinal absorption, bioavailability, and absence of toxicity. Pretreatment with LsHE reduced the area of gastric damage and restored mucus in both ethanol- and indomethacin-induced injury models. In both models, pretreatment increased levels of catalase, glutathione, and superoxide dismutase and reduced levels of malondialdehyde and myeloperoxidase compared with untreated mice. Inhibition of prostaglandin and nitric oxide-related signaling pathways reversed the gastroprotective effect of LsHE in ethanol-induced lesions, but this effect was not fully reversed by blocking potassium channels or transient vanilloid receptors. LsHE was able to increase pH and reduce gastric acidity and secretory volume to levels similar to control animals in a pyloric binding model. Seven days of treatment with LsHE reduced the area and volume of the acetic acid-induced gastric lesion and increased the healing rate compared with untreated rats. LsHE did not promote changes indicative of toxicity. Treatment also increased the levels of catalase and glutathione and reduced the levels of superoxide dismutase, malondialdehyde, and myeloperoxidase compared with untreated mice. In conclusion, LsHE exerts a protective effect against gastric lesions induced by ethanol and indomethacin and a healing effect in gastric lesions induced by acetic acid, and its effect may be related to the increase of gastric mucosal protective factors, modulation of acid secretion, and decreased inflammation in tissues.